2021
DOI: 10.1007/s11356-021-16670-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effect of climate change and financial development on agricultural production in ASEAN-4: the role of renewable energy, institutional quality, and human capital as moderators

Abstract: Assessing the effect of climate change and financial development on agricultural production in ASEAN-4: The role of renewable energy, institutional quality and human capital as moderators

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 79 publications
3
21
0
Order By: Relevance
“…In compliance with the previous literature, nations that tend to consolidate their economic growth without considering the efficiency issues suffer from environmental deterioration (For instance, the studies of Lu (2017), Storm and Schröder (2018), Zhang et al (2019) and Jiang et al (2020)). Also, it is consistent with the preceding literature that shifting toward the deployment of clean power sources ameliorates the quality of the environment (For instance, the studies of Katircioglu (2015), Balogh and Jámbor (2017), Dong et al (2017), Bilan et al (2019) and Chandio et al (2021)).…”
Section: Panel Long-run Estimatorsupporting
confidence: 90%
“…In compliance with the previous literature, nations that tend to consolidate their economic growth without considering the efficiency issues suffer from environmental deterioration (For instance, the studies of Lu (2017), Storm and Schröder (2018), Zhang et al (2019) and Jiang et al (2020)). Also, it is consistent with the preceding literature that shifting toward the deployment of clean power sources ameliorates the quality of the environment (For instance, the studies of Katircioglu (2015), Balogh and Jámbor (2017), Dong et al (2017), Bilan et al (2019) and Chandio et al (2021)).…”
Section: Panel Long-run Estimatorsupporting
confidence: 90%
“…Nitrogen management is considered one of the most vital factors affecting wheat growth ( Chowdhury et al., 2021 ), phenology, and grain yield ( Sabagh, 2021 ). Nitrogen fertilizer, when supplied at appropriate rates, plays a significant role in enhancing crop productivity ( Chandio et al., 2022 ). Good nitrogen fertilization practices, including recommended methods and rates, are extremely vital not only for increasing the crop productivity but also for preserving the soil and eco-friendly health ( Panhwar et al., 2019 ; Shah et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Carbon dioxide emissions were also not significant in the long run. A study in four ASEAN countries from 1990 to 2016 revealed that renewable energy use moderates the effect of carbon emission on agricultural production [10].…”
Section: Discussionmentioning
confidence: 99%
“…The agricultural sector is a strategic economic sector in developing economies, especially in Africa. However, the fight against poverty is seriously threatened by climate change shocks in developing countries where the agriculture industry plays a crucial role in enhancing living conditions and guaranteeing food security [10].…”
Section: Introductionmentioning
confidence: 99%